Bone disorders in type 1 multiple endocrine neoplasia syndrome: A review of clinical data - A. M. Gorbacheva (Научно-практическая ревматология, 2021)
Primary hyperparathyroidism (PHPT) is a result of the parathyroid tumors, usually manifesting by elevated serum parathyroid hormone and hypercalcemia. One of the most common complications of PHPT are bone disorders. It mainly occurs as sporadic disease, while the remaining 5–10% is the component of hereditary syndromes, more often – type 1 multiple endocrine neoplasia syndrome (MEN1). MEN1 is caused by the germinal mutation of the oncosuppressor menin gene, founded in all cells of the human body, including the osteogenic cells. Data on the bone state in MEN1 is limited and contradictory. At the same time, some studies indicate that MEN1-related PHPT differs from sporadic form in bone manifestation, which can be presumably associated with the inadequate functioning of mutant menin. The results of experimental works suggest that menin plays an important role in the metabolism and differentiation of bone cells. This article is a literature review on this problem and contains information on the current clinical data on the bone state in patients with MEN1.